2013
DOI: 10.1371/journal.pone.0062741
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Concentrations of Endocannabinoids and Related Primary Fatty Acid Amides in Patients with Post-Traumatic Stress Disorder

Abstract: BackgroundEndocannabinoids (ECs) and related N-acyl-ethanolamides (NAEs) play important roles in stress response regulation, anxiety and traumatic memories. In view of the evidence that circulating EC levels are elevated under acute mild stressful conditions in humans, we hypothesized that individuals with traumatic stress exposure and post-traumatic stress disorder (PTSD), an anxiety disorder characterized by the inappropriate persistence and uncontrolled retrieval of traumatic memories, show measurable alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
103
3
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 179 publications
(119 citation statements)
references
References 42 publications
12
103
3
1
Order By: Relevance
“…Although emotional enhancement of memory has obvious adaptive value in evolutionary terms, the present findings might also carry important implications for maladapative stress responses. Changes in glucocorticoid (Yehuda, 2009), endocannabinoid (Hauer et al, 2013;Hill et al, 2013;Neumeister et al, 2013), and catecholaminergic (Krystal and Neumeister, 2009) signaling have repeatedly been demonstrated in individuals after malignant stress exposure and the development of posttraumatic stress disorder (PTSD). Critically, a recent study reported that the combined assessment of alterations in cortisol and anandamide levels has a much higher predictive value in classifying PTSD cases than analysis of these factors individually (Neumeister et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Although emotional enhancement of memory has obvious adaptive value in evolutionary terms, the present findings might also carry important implications for maladapative stress responses. Changes in glucocorticoid (Yehuda, 2009), endocannabinoid (Hauer et al, 2013;Hill et al, 2013;Neumeister et al, 2013), and catecholaminergic (Krystal and Neumeister, 2009) signaling have repeatedly been demonstrated in individuals after malignant stress exposure and the development of posttraumatic stress disorder (PTSD). Critically, a recent study reported that the combined assessment of alterations in cortisol and anandamide levels has a much higher predictive value in classifying PTSD cases than analysis of these factors individually (Neumeister et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Further studies also point towards reduced concentrations of some endocannabinoids and related N-acyl-ethanolamides in PTSD Neumeister et al, 2013). However, opposite or null effects have also been reported (Hauer et al, 2013;Schaefer et al, 2014). These inconsistencies might be due to strong variations of plasma endocannabinoid concentrations during the day (Vaughn et al, 2010).…”
Section: Introductionmentioning
confidence: 89%
“…This interaction takes place at two levels: postsynaptically, by increasing the efficacy of the ␤-adrenoceptor-cAMP/PKA system, and presynaptically in the locus coeruleus cell groups that project to the BLA (546). Other interactions of glucocorticoids that might play a role in the modulation of memory, particularly fear memory, are the one with cannabinoids (233), and the one with cholinergic neurons by which glucocorticoids may reprogram the mesopontine cholinergic system (87), which deserves further research because it might represent important physiological functions. ACTH and glucocorticoids are secreted in a circadian fashion (209,269,270).…”
Section: Glucocorticoidsmentioning
confidence: 99%